Efficacy of Photobiomodulation Therapy Utilizing 808 nm and 660 nm Alone and in Combination for Treatment of Paresthesia in Rats - Ehsan Hajesmaelzade; Mohammad Mohammadi; Sina Kakooei; Luca Solimei; Stefano Benedicenti; Nasim Chiniforush (Biomedicines)
Background/Objectives: This study assessed the efficacy of photobiomodulation therapy (PBM) by 808 nm and 660 nm alone and in combination for the treatment of paresthesia in rats. Methods: This animal study was conducted on 36 adult male Wistar rats. After general anesthesia, the facial nerve of the right side of the face of rats was surgically exposed and pinched, returned in place, and sutured. The rats were randomly assigned to six groups (n = 6) of (I) no-intervention (control), (II) no-laser, (III) 808 nm laser (250 mW, 4 W/cm2, 20 s, 8 J/cm2, (IV) 660 nm laser (150 mW, 0.25 W/cm2, 32 s, 8 J/cm2, (V) 808 nm plus 660 nm laser with the original settings, and (VI) 808 nm plus 660 nm laser with half of the time and energy density. After 16 days, a biopsy sample was taken from the nerve injury site and underwent histological, histometric, and immunohistochemical assessments. Results: Significantly lower edema and congestion were seen in the combined laser group with original settings (p < 0.05); this group had no significant difference with the control group regarding degenerative changes of the nerve fibers and Schwann cells (p > 0.05). The 660 nm, and combined laser groups, had a significantly lower accumulation of inflammatory cells (p < 0.05). The number of blood vessels in combined laser groups was significantly lower than that in the no-laser group (p < 0.05). Conclusions: The results showed the positive efficacy of PBM by 808 nm and 660 nm lasers in resolution of inflammation and reduction of degenerative changes of Schwann cells and nerve fibers.